The impact of puff frequency on respirable particulate matter in mainstream cigarette smoke. (31st January 2023) - Maiyo, Alfayo K.; Korir, Benjamin K.; Kibet, Joshua K.
Abstract: Background: Inhalation of particulate matter (PM) from cigarette smoke is hazardous to smokers and non‐smokers. This contribution simulates the deposition of cigarette PM on the lung surface by trapping tobacco smoke particulates on Croton megalocarpus biochar. This study investigated one commercial cigarette (MM) and one local cigarette (RR). Methodology: Biochar was incorporated into the filters of MM and RR cigarettes in order to adsorb PM from mainstream cigarette smoke. A weighed 5 mg of biochar with adsorbed cigarette PM was analyzed using a scanning electron microscope and a Fourier transform infrared spectrometer. The size distribution of cigarette smoke particulates was processed using ImageJ software. Results: At 15 s puff time, the mean particulate diameters for the commercial and the local cigarettes, respectively, can be classified as coarse ≈ PM10 . Conversely, the mean particulate diameter at 2 s puff time for the commercial cigarette falls under the ultrafine classification of ≤PM2.5, whereas at the same puff time, the mean particulate diameter for the local cigarette was approximately PM2.5 . Data from Fourier transform infrared spectroscopy indicate the PM in the two model cigarettes contains aromatic structures that feature the C=C bond characterized by an intense absorption band at δs (1600 cm −1 ). Conclusions: This study found that PM in mainstream cigarette smoke depends on puff time. Although cigarette smoking was conducted for two model cigarettes, this study can be extended to any other form of cigarette. Moreover, this study emphasizes the need for comprehensive studies on real‐world cigarette smoking conditions, taking into account cigarette smokers who use larger puff volumes. Abstract : Tobacco smoke is a toxic gas‐phase cocktail consisting of a broad range of particulate matter (PM) comprising organics, metals, and free radical intermediates. Airborne PM is one important aspect of grave health concerns. Fine particles with an aerodynamic diameter of less than 2.5 μm are considered fatal because they can penetrate deeper areas of the human respiratory airway and even the blood circulatory system.